FORMULATION OF GUMMY CANDY PREPARATIONS CONTAINING CHIA SEED OIL (Salvia hispanica L.) - Taufik, Hidayat; Alna, Salsabila; Firman, Gustaman; Alika Rahma, Kalimatillah (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Perjuangan Tasikmalaya, 2026)
Gummy candy is a type of soft ceonfection that utilizes gelatin as a gelling agent, resulting in a characteristic chewy texture. Chia seed oil (Salvia hispanica L.) was used as the active ingredient due to its high alpha-linolenic acid content. This study aims to determine the formula and characteristics of good gummy candy with varying concentrations of chia seed oil and gelatin and to determine the level of preference among children. The prepared gummy candies were evaluated for organoleptic properties, pH, weight uniformity, moisture content, and texture profile analysis. The results showed that all formulations produced bear-shaped gummy candies with a sweet taste and varying colors. The pH values ranged from 4.51 to 4.88, and all formulations met the weight uniformity requirements. Texture profile analysis showed that increasing gelatin concentration resulted in higher hardness and chewiness. Hedonic testing revealed no significant differences (p > 0.05) among the three formulations in terms of color, aroma, and taste, indicating that all formulations were equally acceptable to the panelists. In conclusion, chia seed oil can be successfully formulated into gummy candy preparations, and variations in gelatin concentration influence the physical texture characteristics without significantly affecting consumer preference.